Investigation of Deuterium Implantation into Beryllium Sample by Electron Energy Loss Spectroscopy. (October 2017) - Afanas'ev, V P; Gryazev, A S; Kaplya, P S; Köppen, M; Ridzel, O Yu; Subbotin, N Yu; Hansen, P
Abstract: Quantitative analysis of hydrogen isotopes in first wall as well as in construction materials of future fusion devices plays a crucial role to understand the evolution of those materials under operation conditions. A quantitative understanding of hydrogen in materials is also an important issue for storing energy as well as for fuel cells. A combination of Electron Energy Loss Spectroscopy (EELS) and Elastic Peak Electron Spectroscopy (EPES) is presented in this study to tackle these problems of modern material research for energy production and storage. Accurate inelastic scattering background subtraction is a key part of the presented quantitative measurement of the Be/D ratio. The differential inelastic scattering cross-section is determined by the fitting procedure. The fitting procedure is based on the iterative solution of the direct problem and minimization of the residual between computed and measured spectra. This study also takes into account the difference in electron energy loss laws for surface and bulk. The inelastic scattering cross-sections for different doses of deuterium ions in beryllium substrate (5.5·10 21 m −2 and 2.01·10 22 m −2 ) were defined in a two-layered model. The analysis is carried out for the EELS spectra. Relative concentration of D atoms is defined.